Managing uncertainty in organizational communication - Kramer, Michael W. (LEA's communication series., 2004)
In this book, Michael W. Kramer applies uncertainty reduction theory (URT)--a key theory in current communication scholarship--to the context of organizational communication. Examining URT and the range of research applicable to organizational settings, Kramer proposes a groundbreaking theory of managing uncertainty (TMU), which synthesizes prior research while also addressing its criticisms.